The Evaluation of Handicrafts and Entrepreneurship Learning Process at SMAN 1 Kerambitan - Asih, Ni Made Utami; Setemen, Komang; Artanayasa, I Wayan; Widiartini, Ni Ketut (Graduate Program Magister Manajemen Pendidikan, 2023)
This study aimed at evaluating the implementation of Handicraft and Entrepreneurship course at SMAN 1 Kerambitan. Mix-Method approach was adapted in the form of CIPP evaluation model as the research design which made this study was different from other researches. There were 125 participants consisted of teachers, staffs, and students involved as a research sample. They were selected by using random sampling technique. The data were obtained through questionnaire, observation, and document analysis. The research instruments used were questionnaire and check-list. The data were analyzed quantitatively and qualitatively. The results showed that all the dimensions; context, input, process, and product of Handicraft and Entrepreneurship course at SMAN 1 Kerambitan were in an excellent level. The evaluation dimensions of the current study implicated that the implementation of handicrafts and entrepreneurship allowing teachers to innovate the learning process in improving students’ creativity to produce a unique handicraft product.